Effectiveness of integrase strand transfer inhibitors in HIV-infected treatment-experienced individuals across Europe - EuResist Network, INTEGRATE study group (2022)
Funding Information: The INTEGRATE project received an unconditioned grant from Gilead Sciences Europe Ltd. This study was also funded by the Swedish Research Council (2016‐01675, to AS), the European Union by the CARE H2020 project (under grant agreement no. 825673) and Stockholm County Council (ALF 20190451 and CIMED 20200645; to AS), and the Fundação para a Ciência e Tecnologia, Portugal (INTEGRIV Project PTDC/SAU‐INF/31990/20170 and GHTM‐UID/Multi/04413/2013; to AA). Funding Information: The INTEGRATE project received an unconditioned grant from Gilead Sciences Europe Ltd. This study was also funded by the Swedish Research Council (2016-01675, to AS), the European Union by the CARE H2020 project (under grant agreement no. 825673) and Stockholm County Council (ALF 20190451 and CIMED 20200645; to AS), and the Fundação para a Ciência e Tecnologia, Portugal (INTEGRIV Project PTDC/SAU-INF/31990/20170 and GHTM-UID/Multi/04413/2013; to AA). The INTEGRATE study group: A. Abecasis, Global Health and Tropical Medicine (GHTM), Instituto de Higiene e Medicina Tropical - Universidade Nova de Lisboa, Lisbon, Portugal M. Bobkova, Gamaleya Federal Center for Epidemiology and Microbiology of Russia C. Seguin-Devaux, Department of Infection and Immunity, Luxembourg Institute of Health, Luxembourg M. Fabbiani, University Hospital of Siena, Siena, Italy F. Garcia, Hospital Universitario San Cecilio, Granada, Spain A. M. Geretti, University of Liverpool, UK P. Gomes, Laboratório de Biologia Molecular (LMCBM, SPC, CHLO-HEM), Lisbon, Portugal and Centro de Investigação Interdisciplinar Egas Moniz (CiiEM), Instituto Universitário Egas Moniz, Caparica, Portugal F. Incardona, EuResist Network, Roma, Italy – IPRO, Roma, Italy R. Kaiser, University of Cologne, Cologne, Germany R. Paredes, Irsicaixa, Spain B. Rossetti, University Hospital of Siena, Siena, Italy M. Sayan, Kocaeli University, Medical Faculty, Turkey A. Sönnerborg, Karolinska Institutet, Stockholm, Sweden A. M. Vandamme, REGA Institut KU Leuven, Belgium M. Zazzi, University of Siena, Siena, Italy. Publisher Copyright: © 2022 British HIV Association.